Peran Ta'dzim dan Khidmah dalam Implementasi Karakter Sosial Siswa Santri Mts - Devia Mar'atu Lutfi; Khoirul Anwar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the forms of ta'dzim and khidmah traditions carried out by ninth-grade students at MTs Riyadlus Sholihin Al-Islamy, and to examine the role and contribution of these two traditions in the formation of social character which includes respect, responsibility, social concern, and cooperation. The study used a mixed methods approach with a concurrent triangulation design. Data were collected through participant observation, in-depth interviews, and a Likert-scale questionnaire consisting of 24 statements from 22 respondents. Quantitative data analysis used descriptive statistics, while qualitative data were analyzed through the Miles, Huberman, and Saldaña model. The results of the instrument test showed that all items were valid (r-count 0.435–0.739 > r-table 0.432) and reliable (Cronbach's Alpha = 0.814). Descriptive analysis shows that the ta'dzim variable obtained an average of 29.09 (90.9%), khidmah 24.50 (87.5%), and social character 32.36 (89.9%), all in the high category. The conclusion of the study shows that ta'dzim practices that instill an attitude of respect and responsibility and khidmah practices that develop social awareness and cooperation synergistically contribute to the formation of a strong social character of students. This study strengthens the position of Islamic boarding schools as a model of character education that is relevant to the values ​​of the Pancasila Student Profile. Keywords: Khidmah, Pesantren, Social Character, Social Studies Education, Ta'dzim